The year in cardiology: coronary interventions - Baumbach, Andreas; Bourantas, Christos; Serruys, Patrick; Wijns, William (SA Heart Journal, 2020)
Percutaneous coronary intervention (PCI) research focuses on the optimisation of treatment strategies, the development of novel equipment and pharmacotherapies for improved results, and on risk stratification and identification of high-risk patients that will benefit from emerging therapies targeting atherosclerotic evolution. Over the last year, important clinical studies have been reported that examined the efficacy of different treatment strategies and stent platforms in patients with obstructive coronary artery disease (CAD), and guidelines have been published to provide recommendations about the management of these patients. The aim of this article is to summarise the findings of the pivotal studies published in 2019 and to discuss their impact on clinical practice.